Recent Advances in Infective Endocarditis - Kerrigan, Steven W. (IntechOpen, 2013)
Endocarditis is an inflammation of the lining of the heart and valves. It can be due to a non-infectious cause but when the inflammation is associated with an infection, usually bacterial, it is known as infective endocarditis. It is typically characterized by the development of a large septic thrombus on one of the cardiac valves. As this thrombus grows, it can lead to valve failure or may fragment forming a septic embolus that is associated with high mortality if the target of the embolus is the brain, heart or lung. This book reviews multi-organ complications associated with Infective endocarditis including significant recent advances in molecular mechanisms underlying thrombus formation on the cardiac valve, anti-microbial treatment and surgery.